Pemenuhan Hak Anak Sebagai Korban dalam Sistem Pengadilan Tindak Pidana Kekerasan Seksual - Siahaan, Rahel; Tan, Winsherly; Febriani, Emiliya (Legal Standing : Jurnal Ilmu Hukum, 2025)
This study aims to analyze the effectiveness of fulfilling children's rights in the judicial system of sexual violence crimes in Batam City, as well as to identify the challenges and realities faced during its implementation. The research method used is an empirical juridical approach, with data collected through in-depth interviews with law enforcement officials, including investigators and police in Batam City. The findings reveal that although comprehensive regulations exist, their implementation remains suboptimal due to limited human resources, insufficient child-friendly facilities, and ineffective inter-agency coordination. These barriers hinder the protection and recovery of child victims of sexual violence. The study also highlights the importance of applying the principles of Best Interests of the Child and the Restorative Justice approach to create a more child-friendly judicial system. Therefore, improvements in law enforcement training, strengthening inter-agency coordination, and developing facilities to support the recovery of child victims of sexual violence are urgently needed.